Association between dietary inflammatory index and atherosclerosis cardiovascular disease in U.S. adults - Zhang, Jie; Jia, Jundi; Lai, Runmin; Wang, Xinyi; Chen, Xuanye; Tian, Wende; Liu, Qiyu; Li, Jingen; Ju, Jianqing; Xu, Hao (Frontiers in Nutrition, 2023)
Objective To evaluate the association between dietary inflammatory index (DII) and Atherosclerotic cardiovascular disease (ASCVD) among U.S. adults. Methods We collected data from National Health and Nutrition Examination Survey (NHANES) between 1999 and 2018. Adults who reported complete information to diagnose ASCVD and calculate DII were included. We used three models to differentially adjust the covariates, including age, sex, race or ethnicity, education level, smoking status, poverty, insurance, body mass index, hyperlipemia, hypertension, and diabetes. Logistic regression was used to estimate the Odds Ratio (OR) and 95% confidence interval (95% CI) for ASCVD grouped by DII deciles. We additionally conducted spline smoothing with the generalized additive model (GAM) and the log-likelihood ratio to examine the non-linear relationship between DII and ASCVD. If exists, the segmented linear regression will be used to detect the cutoff point. The subgroup analyses were stratified by various atherosclerotic cardiovascular diseases (i.e., CHD, angina, heart attack, and stroke) and sex. Results A total of 48,733 participants (mean age, 47.13 ± 0.19 years) with 51.91% women were enrolled, of which 5,011 were diagnosed with ASCVD. In the crude model, participants in the five highest deciles (D6, 7, 8, 9, and 10) of DII score had a significantly higher risk of having ASCVD compared to those in the first decile. In the fully adjusted model, those in the tenth decile [OR = 1.47, 95% CI = (1.18,1.84)] of DII had a significantly increased risk of ASCVD compared to the first decile. Notably, when DII is above 3, the ASCVD risk increased by 41% for each one increase in DII [OR = 1.41, 95% CI = (1.15,1.73)]. This relationship was more pronounced in females. Conclusion Our study revealed a positive and non-linearly association between DII and ASCVD in U.S. adults. This relationship was more pronounced in females. The findings provide a reference for future research and diet recommendations.